Identification of rare high-risk copy number variants affecting the dopamine transporter gene in mental disorders - Høffding, Louise K.; Sobanski, Esther; Witt, Stephanie (Nordic journal of psychiatry, 2016)
Background: The dopamine transporter, also known as solute carrier 6A3 (SLC6A3), plays an important role in synaptic transmission by regulating the reuptake of dopamine in the synapses. In line with this, variations in the gene encoding this transporter have been linked to both schizophrenia and affective disorders. Recently, copy number variants (CNVs) inSLC6A3have been identified in healthy subjects but so far, the implication of CNVs affecting this gene in psychiatric diseases has not been addressed.Aims: In the present study, we aimed to investigate whether CNVs affectingSLC6A3represent rare high-risk variants of psychiatric disorders.Methods: We performed a systematic screening for CNVs affectingSLC6A3in 761 healthy controls, 672 schizophrenia patients, and 194 patients with bipolar disorder in addition to 253 family members from six large pedigrees affected by mental disorders using single nucleotide polymorphism arrays and subsequent verification by real-time polymerase chain reaction.Results: We identified two duplications and one deletion affectingSLC6A3in the patients, while no such CNVs were identified in any of the controls. The identified CNVs were of different sizes and two affected several genes in addition toSLC6A3.Conclusion: Our findings suggest that rare high-risk CNVs affecting the gene encoding the dopamine transporter contribute to the pathogenesis of schizophrenia and affective disorders.
Gesehen am 07.05.2019
Published online11 November 2015